Hybrid Panel Board from Coconut Fibre & Glass Fibre - Ahmad Kamel, Muhammad Hazmie Heizran; Jalaluddin, Muhammad Naufal Hazim; Mohamad Sufian, Nur Muhamad; Norhayati Ngadiman (Multidisciplinary Applied Research and Innovation, 2024)
According to previous studies, panel board made from coconut fibre will more easily absorb water and cause the panel board material to expand. Meanwhile, fibreglass panel board have some drawbacks such as being too heavy to carry anywhere. In order to solve this issue, fibreglass and coconut fibre are used as the primary raw materials in hybrid panel board in place of standard panel board. It is expected that this project will improve the quality of the hybrid panel board on three main parameters; mechanical strength, water resistance, and soundproofing. 5 methods will be used to achieve the objective of this research. The first method of testing is the Modulus of Rupture (MOR) and Modulus of Elasticity (MOE) to test the mechanical strength of panel boards. Next, a swelling test and water absorption test to assess the absorption ability. The last method is a soundproof test. For mechanical strength, a hybrid panel is better than a coconut fibre panel board and plywood but less than a fiberglass panel board. Furthermore, fiberglass has a lower percentage of water resistance than hybrid panel boards but better than coconut fibre and conventional panel boards. Last but not least, hybrid panel boards outperform plywood and coconut fibre panel boards but fall short of fibreglass panel boards.